Plan de desarrollo turístico para la parroquia Isinliví del cantón Sigchos, provincia de Cotopaxi. - Durán Castellano, Jerson Alexis (2023)
The present investigation called "Tourism development plan for the Isinliví parish, Sigchos canton, Cotopaxi province", the qualitative approach methodology was used in which different objectives are developed; For the fulfillment of the first objective, as a result, the situational and tourist diagnosis of the study area was identified, the reality of the local situation in which the parish was found, the lack of a tourism development plan for the parish; Regarding the second objective, field trips were carried out to identify the tourist, cultural and natural attractions of the parish through the use of files as a research instrument for the collection of information using the MINTUR methodology, fourteen attractions are diagnosed, being eleven cultural, Church of Cochalo Isinliví, the Wedding, Feast of San Juan, Church of Hierba Buena, Church of Guangomalag, Old Mill of Cumbijin, Church of Guantolo, Church of the province, Mirador el Calvario, Don Bosco Artistic Center and three Natural resources, Laguna de Tiliche, the five waterfalls of Guangomalag, Cerro de Hierba Buena, as a result, the tourist inventory of the Isinliví parish was obtained. For the scope of the third objective, the descriptive method was used, with this the matrix of problems was developed, helping to identify the tourist difficulties, this will later help the elaboration of a SWOT and crossed SWOT, strengths and weaknesses were obtained, opportunities, threats that it has. Thanks to these results, the parish can evaluate external factors (MEFE) and internal factors (MEFI), programs and projects that guide the tourism development of the Isinlivì parish.